(untitled) (Medicine Today, 2024)
Introduction: Reduction in the glomerular filtration rate (GFR) can act as a risk factor for causing cardiovascular abnormalities. Various cardiac abnormalities can complicate chronic kidney disease which range from concentric left ventricular hypertrophy to dilated cardiomyopathy. Aim: To enlist the echocardiographic findings of chronic kidney disease patients. Materials and Methods: This observational cross-sectional study was conducted in the cardiology unit of Rangpur Medical College Hospital between August 2022 to August 2023. A total of 88 patients of CKD were included in the analysis. Two-dimensional transthoracic echocardiography was done in each patient for LV study. Results: The mean age of the patients was 43.32±10.67 years. There was male dominance with male/female ratio 1.9. LV systolic dysfunction was diagnosed in 44%(39/88) of patients, LV diastolic dysfunction in 65.5%(55/88) patients, and concentric left ventricular hypertrophy (LVH) in 68%(60/88) of patients. Also DCM in 17% and IHD and pericardial effusion both in 15% of CKD patients. Conclusion : Concentric LVH is the most common structural defect in CKD patients followed by LV diastolic dysfunction, LV systolic dysfunction, Ischaemic heart disease, dilated cardiomyopathy and pericardial effusion. Medicine Today 2024, Vol.36 (2): 104-106